Redundantly grouped cross-object coding for repairable storage - Datta, Anwitaman (2012)
The problem of replenishing redundancy in erasure code based fault-tolerant storage has received a great deal of attention recently, leading to the design of several new coding techniques [3], aiming at a better repairability. In this paper, we adopt a different point of view, by proposing to code across different already encoded objects to alleviate the repair problem. We show that the addition of parity pieces - the simplest form of coding - significantly boosts repairability without sacrificing fault-tolerance for equivalent storage overhead. The simplicity of our approach as well as its reliance on time-tested techniques makes it readily deployable.